The Effect of Facilities and Infrastructure Quality on Student Satisfaction at Faculty of Social and Political Sciences, State University of Surabaya - Zahra Prima Putri Regina; Azzahra Anindya Krisna Putri; Devi Artika Sari; Irma Oktavia Sari; Maghfiroh Hefril Gatmalia; Tauran Tauran; Ardiyansah Ardiyansah (Master of Public Administration FISIPOL Universitas Negeri Surabaya, 2026)
This study examines the effect of educational facilities and infrastructure quality on student satisfaction at the Faculty of Social and Political Sciences, State University of Surabaya, recognizing that physical learning environments are essential components in supporting effective higher education services. The research employs a quantitative approach with an explanatory survey design to analyze the causal relationship between facility quality and student satisfaction. The sample consisted of 125 respondents selected through proportional random sampling from a population of 4,060 undergraduate students from the 2024 and 2025 cohorts. Data were collected using a structured questionnaire developed based on the five dimensions of the SERVQUAL model: tangibles, reliability, responsiveness, assurance, and empathy. Statistical analysis was conducted using simple linear regression with SPSS version 25. The findings indicate that the overall quality of educational facilities and infrastructure is categorized as good, although several aspects, including parking areas, student discussion spaces, and facility maintenance, require substantial improvement. Student satisfaction is categorized as moderately high, reflecting that existing facilities generally meet students’ expectations and academic needs. The regression analysis produced the equation Y = 5.020 + 0.278X, with a t-value of 11.421 and a significance level of 0.001, confirming a positive and statistically significant relationship between facility quality and student satisfaction. The coefficient of determination (R² = 0.515) indicates that 51.5 percent of student satisfaction is influenced by facility quality. The study emphasizes the importance of continuous infrastructure improvement and responsive campus management to enhance student satisfaction and institutional reputation.